Intersex goats show different gene expression levels in the hypothalamus and pituitary compared with non‐intersex goats based on RNA‐Seq. Issue 1 (25th November 2021) - Han, Haoyuan; Yang, Shuai; Li, Jun; Zhao, Jinyan; Wei, Hongfang; Ha, Si; Li, Wantao; Li, Congcong; Quan, Kai
Abstract: The conditions for sex reversal in vertebrate species have been extensively studied, and the results highlighted numerous key factors involved in sex differentiation. However, the transcriptomes in hypothalamic and pituitary tissues from intersex goats have rarely been studied. The aim of this study was to screen candidate genes and signalling pathways related to sex reversal in Huai goats by analyzing gene expression in hypothalamic and pituitary tissues via transcriptome sequencing and bioinformatics analyses. In total, 612 and 139 differentially expressed genes (DEGs) were identified between the intersex and non‐intersex groups in the hypothalamus and pituitary, respectively. The DEGs in the hypothalamus and pituitary were significantly enriched in 41 and 16 signalling pathways, respectively, including the calcium signalling pathway, neuroactive ligand‐receptor interaction signalling pathway, and oestrogen signalling pathway, which might be related to intersex sex development disorders. A candidate gene from the tachykinin family (TACR1) was significantly enriched in the calcium signalling pathway. Thirty‐one DEGs were shared between these two comparisons and were enriched in several acetyl‐CoA‐related processes and the oestrogen signalling pathway. The results of the real‐time PCR analysis show that the transcriptome sequencing results were reliable. The transcriptome data indicate that the regulation of various physiological systems is involved in intersex goat development. Therefore, these results provide helpful data enhancing our understanding of the molecular mechanisms underlying intersex syndrome in goats. Abstract : Our study compared the gene expression profiles of hypothalamus and pituitary tissues from intersex and normal goats. And 31 genes were shared between these two sets of comparisons. These genes were enriched in the oestrogen signalling pathway and acetyl‐CoA biosynthetic process, suggesting that they might exhibit important functions in the regulation of hormone biosynthesis related to gonad development.